Inetetamab triggers cardiotoxicity through its interaction with apoptosis, oxidative stress and autophagy pathways - Weiqun Wang; Hongliang Zhang; Yikun Qu; Yue Li; Peng Peng; Chengbo Lu; Xinyue Zhao; Ziteng Cai; Chaonan Peng; Xiaoli Guo; Yuxin Guo; Jie Li; et al. (Scientific Reports)
Abstract Inetetamab, a trastuzumab biosimilar, has obtained approval for the treatment of HER2-positive advanced metastatic breast cancer. Despite studies indicating its cardiotoxic properties, the intricate mechanisms underlying its toxicity remain elusive. In the present study, we demonstrated in vitro that exogenous administration of Inetetamab triggered injury in H9c2 myocardial cells, characterized by a significant decrease in cell viability and noticeable morphological changes. Furthermore, exogenous exposure to Inetetamab elicited a series of toxic effects within H9c2 cells, notably promoting apoptosis and autophagy, diminishing the mitochondrial membrane potential (DCm), and elevating intracellular ROS production. Concurrently, there was a notable decrease in intracellular MDA generation, accompanied by disruption of the GSH/GSSG balance. In vivo mouse model, Inetetamab administration prominently induced cardiomyocyte injury, characterized by the pathological change in the myocardial tissue and a marked elevation in serum levels of creatine kinase isoenzyme (CK-MB), brain natriuretic peptide (BNP) and cardiac troponin I (cTnI). Similarly, Inetetamab administration also initiated cardiomyocyte apoptosis and oxidative stress injury in vivo. Furthermore, Inetetamab administration significantly modulated the expression of apoptosis- and autophagy-related proteins both in vivo and in vitro. Our study highlights Inetetamab induces cardiotoxicity by affecting apoptosis, oxidative stress and autophagy.